1966
DOI: 10.1149/1.2424161
|View full text |Cite
|
Sign up to set email alerts
|

Optical Studies of Electrolyte Films on Gas Electrodes

Abstract: The geometry of stable electrolyte films has been established on nickel and silver surfaces partially immersed in aqueous caustic solutions. Such films, which are very sensitive to factors affecting interfacial energies and may be useful for their determination, appear to be important for the mass transfer in certain gas diffusion electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…14 With an alkaline electrolyte, interesting interfacial phenomena have been observed. [15][16][17][18][19][20][21] In a previous study, we observed an in situ meniscus motion during the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) on a platinum electrode. 17 A spread of the three-phase interface during the ORR was observed and the role of hydroxide ions in determining the surface tension was investigated.…”
mentioning
confidence: 99%
“…14 With an alkaline electrolyte, interesting interfacial phenomena have been observed. [15][16][17][18][19][20][21] In a previous study, we observed an in situ meniscus motion during the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) on a platinum electrode. 17 A spread of the three-phase interface during the ORR was observed and the role of hydroxide ions in determining the surface tension was investigated.…”
mentioning
confidence: 99%
“…As determined quantitatively in the case of metal]gas electrodes in alkaline solutions (12,13), such films can extend over distances which exceed the meniscus height (a few mm) by several orders of magnitude. As determined quantitatively in the case of metal]gas electrodes in alkaline solutions (12,13), such films can extend over distances which exceed the meniscus height (a few mm) by several orders of magnitude.…”
mentioning
confidence: 89%
“…For high-energy surfaces the ^"Potential or surface potential or contact potential will influence the surface tensions and hence 9 [397,440]. From the phenomena observed with model porous electrodes (mostly cylindrical capillaries), which we will not discuss here, it is clear that electrochemical processes occurring at the surface may result in an increase as well as a decrease of 9 (see [440][441][442][443][444]). Further, it is well known that the C-potential of mineral surfaces depends strongly on the pre-treatment of the surface and, m general, displays a time effect when aged in water [R445].…”
Section: 82 Liquid Penetrates Solid or Filmmentioning
confidence: 99%
“…Evaporation may further cause a change in film properties when there is more than one component present in the film. These effects can be compared with and could be aggravated by the Marangoni phenomena caused by preferential evaporation [452,453], temperature gradients [453,454] and electro-osmotic gradients [442,443,455]. Probably, thfe phenomena reported by Hardy [456] and Bangham [39 9,427], concerning the sensitivity of 9 to the presence of a second adsorbable compound, fall into this class.…”
Section: 84 De-or Replacement Of Adsorbed Filmsmentioning
confidence: 99%